2000
DOI: 10.1097/00005392-200008000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Prostate Cancer Characteristics at Radical Prostatectomy After Population Based Screening

Abstract: Screening for prostate cancer leads to an increase in surgical treatment for relatively small tumors that have a higher probability of being organ confined. Although the frequency of positive lymph nodes at operation decreases dramatically and the proportion of organ confined tumors after surgery increases, there is a shift from Gleason 8 to 10 tumors towards lower grade tumors at radical prostatectomy. Still, judged by the high frequency of focal dedifferentiation in screen detected tumors, most of them and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…14,15,17,18 A recent analysis compared the pathologic stage and grade of tumors detected by PSA-based screening to historical cancers detected by needle biopsy or TURP. 19 The authors found that screen-detected cancers were more likely to be pathologically organ confined and less likely to be Gleason score 8 -10 tumors. Nonetheless, a perennial limitation of such investigations is the need for historical comparisons, rather than assessment of a concurrent population of cancers detected for indications other than screening based on PSA levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…14,15,17,18 A recent analysis compared the pathologic stage and grade of tumors detected by PSA-based screening to historical cancers detected by needle biopsy or TURP. 19 The authors found that screen-detected cancers were more likely to be pathologically organ confined and less likely to be Gleason score 8 -10 tumors. Nonetheless, a perennial limitation of such investigations is the need for historical comparisons, rather than assessment of a concurrent population of cancers detected for indications other than screening based on PSA levels.…”
Section: Discussionmentioning
confidence: 98%
“…1,4 -7 Furthermore, this migration has been attributed primarily to the impact of widespread prostate carcinoma screening initiatives. 14,[15][16][17][18][19] To date, however, efforts to validate, on a national level, the associations between screening and stage/grade migration have been limited to large screening studies that lacked comparable control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest to histopathologists is the morphological comparison of screen‐detected and non‐screen‐detected cancers in radical prostatectomy specimens. It appears that serum PSA‐detected cancers are more commonly organ‐confined microscopically than those detected outwith screening programmes8, 13, 25–27.…”
Section: Serum Psa – Observational Studies Of Screeningmentioning
confidence: 99%
“…The use of PSA testing has been estimated to provide a diagnostic lead-time of up to 10 years (7)(8)(9)(10)(11). In the mid to late 1980s only one third of prostate cancers were diagnosed at curable stages compared with today when 80% are staged clinically as organ-confined and potentially curable (12)(13)(14). Unfortunately, however, even when the tumour is thought to be localized, up to 25% of men have non-localised disease which declares itself subsequently (15).…”
Section: Introductionmentioning
confidence: 99%